2008
DOI: 10.1353/hpu.2008.0016
|View full text |Cite
|
Sign up to set email alerts
|

Project HEAL: Peer Education Leads to Weight Loss in Harlem

Abstract: Background-Obesity and diabetes are epidemic in the predominantly minority Harlem community. To address them, a coalition of community and academic leaders tested the effectiveness of a peer-led weight loss course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(114 citation statements)
references
References 57 publications
3
110
1
Order By: Relevance
“…We used a specific faith-based approach that focused on the needs of AA congregants in the USA South. Although intervention studies in AA churches have taken place in other regions of the country [11,3840], it is unclear if our approach could be successfully translated elsewhere. Second, it is possible that selection bias occurred since one investigator, well known by the target population, helped in church recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…We used a specific faith-based approach that focused on the needs of AA congregants in the USA South. Although intervention studies in AA churches have taken place in other regions of the country [11,3840], it is unclear if our approach could be successfully translated elsewhere. Second, it is possible that selection bias occurred since one investigator, well known by the target population, helped in church recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The LEAN study incorporated elements common among the studies reviewed, including enrolling African American adults with overweight or obesity, embedding religious principles within the intervention, and utilizing lay health advisors (known as 'community health coaches' in LEAN) to deliver the intervention. However, few studies achieved clinically significant weight loss of >3%, [37][38][39][40] including LEAN. Our treatment fidelity data indicated that of the subset of sessions observed, the physical activity component was infrequently implemented and although the actual weight loss content was delivered adequately, there was room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot of the HEAL (Health Eating, Active Lifestyles) program revealed that participants lost weight and maintained a 5% mean weight loss at 1 year follow-up. 60 We are also working to bring about changes in policy by utilizing community and academic leaders and the media to educate policymakers about the need and the opportunities for change. 61 This model can be applied to other communities with low-income and low-literacy minority populations.…”
Section: Discussionmentioning
confidence: 99%